Wear-resistant and corrosion-resistant composite infiltrated layer as well as preparation method and application thereof

By performing swing laser fusing treatment on the surface of the steel material, a stable and uniform zinc permeability layer is formed, which solves the problems of poor corrosion and low surface hardness of steel materials in special environments in the prior art, and achieves higher wear resistance and corrosion resistance.

CN119663168APending Publication Date: 2025-03-21STEJT GRID ELEKTRIK PAUER INZHINIRING RISERCH INSTITYUT KO LTD +3
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411851645.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing steel materials are prone to corrosion in high humidity, acidic or alkaline environments, and the surface hardness and roughness after zinc permeation are low, affecting wear resistance.

Method used

Laser fusing treatment with different swing trajectories is used to form a more stable and uniform zinc seepage layer, which improves the depth of zinc seepage, and refines the grain structure to increase the hardness and wear resistance of the zinc seepage layer.

Benefits of technology

It significantly improves the hardness, wear resistance and corrosion resistance of the surface of steel materials, extends the service life, and improves the surface roughness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a composite infiltrated layer as well as a preparation method and application thereof. The preparation method comprises the following steps: carrying out zinc impregnation treatment on a steel matrix by utilizing a zinc impregnation agent; and the steel matrix subjected to zinc impregnation treatment is subjected to swing laser melting treatment, and the abrasion-resistant and corrosion-resistant composite infiltrated layer is obtained. According to the method, laser melting with different swing tracks is carried out, so that the molten pool forms a vortex along the swing path of the laser, a more stable and uniform zincizing layer is formed on the surface of the zincizing steel and iron material, grains are further refined after remelting, and the hardness and wear resistance of the surface of the steel and iron material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heat treatment of steel material surfaces, and in particular to a wear-resistant and corrosion-resistant composite infiltration layer and a preparation method and application thereof. Background Art

[0002] Power fittings are mainly used for connection, support and fixing devices in power transmission and distribution systems. Their working environment is usually affected by natural environment and climatic conditions. Power fittings are located outdoors and are affected by natural environment such as ultraviolet rays, air pollution, salt spray, etc. At the same time, power fittings are exposed to various climatic conditions such as high temperature, low temperature, humidity, wind, rain, snow, etc. These factors will affect the performance and durability of power fittings. Therefore, the wear resistance and corrosion resistance of power fittings are crucial to their long-term service life. In special environments, such as marine environments, acidic or alkaline environments, and high humidity areas, power fittings may face higher corrosion risks. In short, the wear resistance and corrosion resistance of power fittings need to comprehensively consider material selection, coating treatment and working environment to ensure their long-term reliable operation.

[0003] Zinc infiltration technology is a chemical heat treatment process, which is mainly used to improve the corrosion resistance of steel materials in the atmosphere and natural water environment. Powder zinc infiltration is to bury the workpiece in a sealed container containing zinc powder, heat it to a temperature below the melting point of zinc, and diffuse the zinc atoms into the surface of the steel material to form a dense zinc-iron alloy layer. This method is characterized by a uniform infiltration layer, no hydrogen embrittlement and deformation, and is suitable for small parts with complex shapes, such as fasteners, springs, pipes, etc. The main function of zinc infiltration technology is to improve the corrosion resistance of steel materials, and the zinc layer can protect the base metal from environmental factors such as atmospheric and water erosion. However, the hardness and wear resistance of the zinc infiltration workpiece are relatively poor in corrosion resistance. The surface hardness of the corrosion-resistant multi-element alloy zinc layer prepared by the patent application with publication number CN104498868A is about 400HV. It can be used in acidic soil to ensure that only small rust spots appear for more than 8-12 years. However, from this patent application, it can be seen that after the zinc infiltration treatment, the dense zinc-iron alloy layer formed near the substrate in the zinc infiltration layer improves the corrosion resistance of the steel workpiece. The closer the sherardizing layer is to the outer surface, the more zinc content it contains, and the zinc atoms diffuse outward from the substrate and cover the substrate surface, which reduces the substrate surface precision, resulting in a decrease in substrate hardness and poor overall wear resistance. As the insulation time increases from 120 hours to 240 hours, the sherardizing thickness increases from 50 to 60 μm to 80 to 90 μm. The longer the insulation time, the deeper the zinc diffusion depth, and thus the thicker the zinc-iron alloy layer, the better the corrosion resistance of the steel material, but the problems of low surface hardness and high surface roughness need to be further solved. The patent application with publication number CN114875356A introduces carbon powder into the sherardizing agent, and the hardness of the prepared sherardizing workpiece is 350 to 450 HV. The sherardizing sample is tested using an electrochemical workstation, and only slight white rust is found on the surface of the sample after 12 days.

[0004] In order to improve the wear resistance and corrosion resistance of the steel material surface, thereby improving the overall service life of the steel material, the patent application with publication number CN107557536A first performs laser melting treatment on the steel material surface to form a mixed structure of martensite and austenite with fine grains, and then performs zinc infiltration treatment on the steel material surface after laser melting treatment, so that the average microhardness of the steel component surface prepared reaches 500HV, and the neutral salt corrosion resistance time reaches more than 800h, but the surface after zinc infiltration treatment still has a large roughness. The patent application with publication number CN117802447A first performs zinc infiltration treatment on the steel material surface, and then performs laser melting treatment on the steel material surface after zinc infiltration treatment, and the zinc infiltration layer further diffuses into the substrate, so that the hardness of the steel material steel component prepared reaches more than 800HV, and the sample after salt spray for 1000h is not corroded, and the surface roughness is effectively reduced, but there are many pores in the melting area, which reduces its wear resistance. Summary of the invention

[0005] The purpose of the present invention is to provide a wear-resistant and corrosion-resistant composite zinc-diffusion layer and a preparation method and application thereof, so as to overcome the problems existing in the prior art. The present invention performs laser melting with different swinging trajectories, so that the molten pool forms a vortex along the swinging path of the laser, thereby forming a more stable and uniform zinc-diffusion layer on the surface of the steel material after zinc-diffusion, and the grains are further refined after remelting, thereby improving the hardness and wear resistance of the steel material surface.

[0006] The present invention is achieved through the following technical solutions: A method for preparing a wear-resistant and corrosion-resistant composite infiltration layer, wherein the wear-resistant and corrosion-resistant composite infiltration layer is applied to a steel substrate, comprising the following steps: Using a sherardizing agent to sherardize the steel substrate; The steel substrate after the zinc infiltration treatment is subjected to an oscillating laser melting treatment to obtain a wear-resistant and corrosion-resistant composite infiltration layer.

[0007] Furthermore, the material of the steel matrix is ​​35CrMo or Q345R.

[0008] Furthermore, before the steel substrate is subjected to the zinc infiltration treatment, the steel substrate is degreased with ethyl acetate at 300°C to 400°C for 20 to 40 minutes and washed with water, then subjected to laser rust removal and washed with water, and finally dried at 280°C to 350°C for 2-2.5 hours.

[0009] Furthermore, the specific settings of the laser rust removal treatment are: laser power is 100~300W, spot diameter is 4~5mm, scanning speed is 100~200mm / s, and overlap rate is 50%~70%.

[0010] Furthermore, the raw materials for preparing the zirconizing agent include, by mass fraction: 60% to 80% zinc powder, 5% to 15% aluminum powder, 2% to 10% magnesium powder, 1% to 2% ammonium chloride, and the balance is aluminum oxide.

[0011] Furthermore, before the steel substrate is subjected to the sherardizing treatment using the sherardizing agent, the sherardizing agent is prepared using the raw materials for preparing the sherardizing agent. After the sherardizing agent is prepared, the prepared sherardizing agent is dried, and the steel substrate is subjected to the sherardizing treatment using the dried sherardizing agent.

[0012] Furthermore, the drying treatment is specifically as follows: heating the prepared zincizing agent to 250°C to 350°C and keeping it warm for 1 to 2 hours, cooling it to 180°C to 220°C with a heating device and then air cooling it to room temperature.

[0013] Furthermore, the sherardizing treatment is specifically as follows: placing a sherardizing agent on the surface of the steel substrate, the thickness of the sherardizing agent is 5-10 mm, and then placing the sherardizing agent and the steel substrate together in a sherardizing device, heating the temperature to 405°C to 445°C, keeping the temperature for 3 to 5 hours, cooling the sherardizing device to 180°C to 220°C, and then air cooling to room temperature.

[0014] Furthermore, the oscillating laser melting treatment is specifically: performing oscillating laser melting treatment on the surface of the steel substrate after the zinc infiltration treatment, and then air cooling to room temperature, wherein the laser power is 1000~1500W, the oscillation amplitude is 0.5~1.5mm, the oscillation frequency is 100~200Hz, the spot diameter is 2mm or 0.2~0.5mm, the scanning speed is 5~15mm / s, and the overlap rate is 30%~50%.

[0015] Furthermore, during the oscillating laser melting process, the oscillation mode is linear, single circular, double circular, infinite or figure 8.

[0016] A wear-resistant and corrosion-resistant composite infiltration layer is prepared by adopting the above-mentioned preparation method.

[0017] The invention discloses an application of a wear-resistant and corrosion-resistant composite diffusion layer on electric power fittings.

[0018] Compared with the prior art, the present invention has the following beneficial technical effects: The present invention performs an oscillating laser melting treatment. Under the action of laser energy and a high-temperature molten pool, iron atoms further diffuse outward and combine with zinc atoms, thereby increasing the penetration depth of zinc. At the same time, under the oscillation of the oscillating laser, the molten pool forms a vortex along the oscillating path of the laser, causing the molten pool to produce a stirring effect, forming a more stable and uniform zinc-diffused layer on the surface of the steel substrate after zinc-diffusion, and the grains are further refined after remelting. At the same time, rapid cooling of the surface after melting is equivalent to quenching, which increases the hardness of the zinc-diffused layer. On the other hand, it limits the diffusion of zinc atoms out of the steel substrate, improving the surface roughness of the steel substrate. In summary, the present invention can improve the hardness, wear resistance and corrosion resistance of the steel substrate surface.

[0019] Furthermore, the activator in the sherardizing agent is aluminum oxide, which can maintain the looseness of the sherardizing agent and prevent the sherardizing agent from bonding during the sherardizing heating process. The catalyst is ammonium chloride, which makes the steel matrix and the zinc powder fully contact, activates the surface of the steel matrix, generates active atoms, and accelerates the reaction between zinc and iron. The addition of an appropriate amount of aluminum powder allows the surface of the sherardizing layer to generate a zinc-aluminum alloy phase, making the thickness of the sherardizing layer more uniform, and to a certain extent inhibiting the outward diffusion of surface zinc atoms, thereby improving the surface roughness and improving the wear resistance of the sherardizing layer. The unit cell structure of zinc and magnesium is a close-packed hexagonal structure. Under the sherardizing treatment at 405°C to 445°C, both generate corrosion-resistant MgZn on the surface of the sherardizing layer. 2 Mg 2 Zn 11 The zinc-magnesium alloy phase is formed, in which magnesium is mainly concentrated at the weak grain boundaries of zinc, transforming it into a strong grain boundary structure that can hinder the invasion of corrosive substances.

[0020] Furthermore, appropriate laser power can ensure that the rust layer can be effectively removed without damaging the steel substrate. At the same time, the scanning speed and spot diameter are adjusted to ensure that the laser energy is evenly distributed in the area to be treated so that the laser beam can evenly remove the rust layer. In addition, a suitable overlap ratio is set to ensure overlap between scanning paths to ensure that no area is missed and no overtreatment is done. DETAILED DESCRIPTION

[0021] The present invention is described in detail below: The present invention provides a method for preparing a wear-resistant and corrosion-resistant composite zinc-plated layer. The wear-resistant and corrosion-resistant composite zinc-plated layer is applied to a steel substrate. The method can overcome the problem of insufficient overall service life of the steel material and form a specific high-thickness, stable and uniform diffusion zinc-plated layer. The prepared composite zinc-plated layer has the properties of high hardness, strong wear resistance and excellent corrosion resistance.

[0022] The specific steps include: (1) Using a sherardizing agent to perform sherardizing treatment on the steel substrate; (2) The steel substrate after zinc infiltration treatment is subjected to oscillating laser melting treatment to obtain a wear-resistant and corrosion-resistant composite infiltration layer.

[0023] Before using the sherardizing agent to sherardize the steel substrate, first prepare the sherardizing agent: mix the sherardizing agent according to the following components and mass fractions: 60% to 80% zinc powder, 5% to 15% aluminum powder, 2% to 10% magnesium powder, 1% to 2% ammonium chloride, and the balance is aluminum oxide. According to the formula of the sherardizing agent, weigh each component as required and mix them evenly.

[0024] The sherardizing agent is then subjected to high temperature drying treatment, specifically: the sherardizing agent is placed in a sherardizing furnace and heated to 250°C to 350°C, and kept warm for 1 to 2 hours, cooled to 180°C to 220°C with the furnace, and then air-cooled to room temperature to obtain a dry sherardizing agent suitable for preparing a composite infiltration layer.

[0025] Then, the steel substrate (the material of the steel substrate is 35CrMo or Q345R) is pretreated, specifically: the steel substrate is degreased with ethyl acetate at 300℃~400℃ for 20~40 minutes and washed with water, and then laser rust removal is performed with a laser power of 100~300W, a spot diameter of 4~5mm, a scanning speed of 100~200mm / s, an overlap rate of 50~70%, and after washing, it is dried at 280℃~350℃ for 2-2.5 hours.

[0026] In step (1), the steel substrate is subjected to a sherardizing treatment using a sherardizing agent, specifically, the sherardizing agent is placed on the surface of the steel substrate, the sherardizing agent thickness is 5-10 mm, and then the sherardizing agent and the steel substrate are placed in a sherardizing furnace, the temperature is raised to 405°C to 445°C, the temperature is kept for 3 to 5 hours, the furnace is cooled to 180°C to 220°C, and then air-cooled to room temperature.

[0027] The oscillating laser melting treatment in step (2) is specifically: performing oscillating laser melting treatment on the surface of the steel substrate after zinc infiltration, wherein the laser power is 1000-1500 W, the oscillation amplitude is 0.5-1.5 mm, the oscillation frequency is 100-200 Hz, the spot diameter is 2 mm or 0.2-0.5 mm, the scanning speed is 5-15 mm / s, the overlap rate is 30-50%, and during the oscillating laser melting treatment, the oscillation mode is linear, single circular, double circular, infinite or figure 8.

[0028] The present invention first performs a zinc infiltration treatment and then performs an oscillating laser melting treatment, thereby increasing the penetration depth of zinc, forming a more stable and uniform composite infiltration layer, increasing the hardness of the zinc infiltration layer, improving the surface roughness of the substrate, and enhancing the wear resistance and corrosion resistance of the steel material.

[0029] The present invention performs an oscillating laser melting process. Compared with laser melting without oscillation of the laser beam, the periodic oscillation of the laser beam can produce a stirring effect of the molten pool, thereby enhancing the convection movement in the molten pool and reducing the temperature gradient of the molten pool, which is beneficial to refining the grain structure and reducing the porosity, and improving the wear resistance and corrosion resistance of the zinc-diffused layer after laser melting. Through the oscillating laser melting process, under the action of laser energy and high-temperature molten pool, iron atoms further diffuse outward and combine with zinc atoms, thereby increasing the penetration depth of zinc. At the same time, under the action of laser oscillation, the molten pool forms a vortex along the oscillating path of the laser, causing the molten pool to produce a stirring effect, forming a more stable and uniform zinc-diffused layer on the surface of the steel material after zinc-diffusion, and the grains are further refined after remelting. At the same time, the rapid cooling of the surface after melting is equivalent to quenching, which increases the hardness of the zinc-diffused layer. On the other hand, it limits the diffusion of zinc atoms out of the substrate and improves the surface roughness of the substrate. In summary, the oscillating laser melting process improves the hardness, wear resistance and corrosion resistance of the surface of the steel material.

[0030] The wear-resistant and corrosion-resistant composite diffusion layer of the present invention can be applied not only to steel substrates, but also to aluminum alloy substrates, copper substrates, and the like.

[0031] The present invention also provides a wear-resistant and corrosion-resistant composite infiltration layer, which is prepared by the above preparation method.

[0032] The invention also provides an application of a wear-resistant and corrosion-resistant composite infiltration layer on electric power fittings.

[0033] The embodiments of the present invention will be described in detail below in conjunction with the examples. The implementation cases are preferred embodiments of the present invention and should not be used to limit the scope of the present invention. In the following examples, the methods and experimental equipment used are all conventional methods and instruments unless otherwise specified.

[0034] Example 1 A method for preparing a wear-resistant and corrosion-resistant composite infiltration layer comprises the following steps: (1) Prepare the zincizing agent; The sherardizing agent of the wear-resistant and corrosion-resistant composite infiltration layer is mixed according to the following composition and mass fraction: 80% zinc powder, 10% aluminum powder, 2% magnesium powder, 7% aluminum oxide, and 1% ammonium chloride. According to the formula of the sherardizing agent of the wear-resistant and corrosion-resistant composite infiltration layer, each component is weighed as required and mixed evenly.

[0035] (2) Drying the zincizing agent at high temperature; The sherardizing agent is placed in a sherardizing furnace and heated to 300°C, and kept warm for 1 hour, cooled to 200°C with the furnace, and then air-cooled to room temperature to obtain a dry sherardizing agent suitable for preparing a composite sherardizing layer.

[0036] (3) Pretreatment of steel substrate; The steel substrate was degreased with ethyl acetate at 350°C for 30 minutes and washed with water, and then subjected to laser rust removal with a laser power of 200 W, a spot diameter of 4 mm, a scanning speed of 150 mm / s, an overlap rate of 60%, and then dried at 300°C for 2 hours after washing.

[0037] (4) Zinc treatment; The sherardizing agent is placed on the surface of the steel substrate with a thickness of 7 mm. The sherardizing agent and the steel substrate are then placed in a sherardizing furnace together, heated to 425°C, kept warm for 4 hours, cooled to 200°C with the furnace, and then air-cooled to room temperature.

[0038] (5) Oscillating laser melting treatment; The surface of the steel substrate after zinc infiltration was subjected to linear oscillating laser melting treatment, with a laser power of 1200 W, an oscillation amplitude of 0.5 mm, an oscillation frequency of 100 Hz, a spot diameter of 0.3 mm, a scanning speed of 10 mm / s, and an overlap rate of 40%.

[0039] Example 2 A method for preparing a wear-resistant and corrosion-resistant composite infiltration layer comprises the following steps: (1) Prepare the zincizing agent; The sherardizing agent for the wear-resistant and corrosion-resistant composite infiltration layer is mixed according to the following components and mass fractions: 60% zinc powder, 10% aluminum powder, 10% magnesium powder, 18% aluminum oxide, and 2% ammonium chloride. According to the formula of the sherardizing agent for the wear-resistant and corrosion-resistant composite infiltration layer, each component is weighed as required and mixed evenly.

[0040] (2) Drying the zincizing agent at high temperature; The sherardizing agent is placed in a sherardizing furnace and heated to 300°C, and kept warm for 2 hours, cooled to 210°C with the furnace, and then air-cooled to room temperature to obtain a dry sherardizing agent suitable for preparing a composite sherardizing layer.

[0041] (3) Pretreatment of steel substrate; The steel substrate was degreased with ethyl acetate at 350°C for 30 minutes and washed with water, and then subjected to laser rust removal with a laser power of 250W, a spot diameter of 5mm, a scanning speed of 150mm / s, an overlap rate of 60%, and then dried at 320°C for 2.5 hours after washing.

[0042] (4) Zinc treatment; The sherardizing agent is placed on the surface of the steel substrate with a thickness of 8 mm. The sherardizing agent and the steel substrate are then placed in a sherardizing furnace together, heated to 435°C, kept warm for 4 hours, cooled to 210°C with the furnace, and then air-cooled to room temperature.

[0043] (5) Oscillating laser melting treatment; The surface of the steel substrate after zinc infiltration was subjected to circular oscillating laser melting treatment, with a laser power of 1300 W, an oscillation amplitude of 1 mm, an oscillation frequency of 150 Hz, a spot diameter of 0.4 mm, a scanning speed of 10 mm / s, and an overlap rate of 40%.

[0044] Example 3 A method for preparing a wear-resistant and corrosion-resistant composite infiltration layer comprises the following steps: (1) Prepare the zincizing agent; The sherardizing agent for the wear-resistant and corrosion-resistant composite infiltration layer is mixed according to the following components and mass fractions: 65% zinc powder, 15% aluminum powder, 5% magnesium powder, 13% aluminum oxide, and 2% ammonium chloride. According to the formula of the sherardizing agent for the wear-resistant and corrosion-resistant composite infiltration layer, each component is weighed as required and mixed evenly.

[0045] (2) Drying the zincizing agent at high temperature; The sherardizing agent is placed in a sherardizing furnace and heated to 350°C, and kept warm for 2 hours, cooled to 220°C with the furnace, and then air-cooled to room temperature to obtain a dry sherardizing agent suitable for preparing a composite sherardizing layer.

[0046] (3) Pretreatment of steel substrate; The steel substrate was degreased with ethyl acetate at 400°C for 40 minutes and washed with water, and then subjected to laser rust removal with a laser power of 300 W, a spot diameter of 5 mm, a scanning speed of 200 mm / s, an overlap rate of 70%, and then dried at 350°C for 2.5 hours after washing.

[0047] (4) Zinc treatment; The sherardizing agent is placed on the surface of the steel substrate with a thickness of 10 mm. The sherardizing agent and the steel substrate are then placed in a sherardizing furnace together, heated to 445°C, kept warm for 5 hours, cooled to 2200°C with the furnace, and then air-cooled to room temperature.

[0048] (5) Oscillating laser melting treatment; The surface of the steel substrate after zinc infiltration was subjected to infinite oscillating laser melting treatment, with a laser power of 1500W, an oscillation amplitude of 1.5mm, an oscillation frequency of 000Hz, a spot diameter of 0.5mm, a scanning speed of 15mm / s, and an overlap rate of 50%.

[0049] Comparative Example A method for preparing a composite infiltration layer comprises the following steps: (1) Prepare the zincizing agent; The sherardizing agent for the wear-resistant and corrosion-resistant composite infiltration layer is mixed according to the following components and mass fractions: zinc powder is 70%, aluminum powder is 5%, magnesium powder is 8%, aluminum oxide is 16%, and ammonium chloride is 1%. According to the formula of the sherardizing agent for the wear-resistant and corrosion-resistant composite infiltration layer, each component is weighed as required and mixed evenly.

[0050] (2) Drying the zincizing agent at high temperature; The sherardizing agent is placed in a sherardizing furnace and heated to 250°C, and kept warm for 1 hour, cooled to 180°C with the furnace, and then air-cooled to room temperature to obtain a dry sherardizing agent suitable for preparing a composite sherardizing layer.

[0051] (3) Pretreatment of steel substrate; The steel substrate was degreased with ethyl acetate at 300°C for 20 minutes and washed with water, and then subjected to laser rust removal with a laser power of 100 W, a spot diameter of 4 mm, a scanning speed of 100 mm / s, an overlap rate of 50%, and then dried at 280°C for 2 hours after washing.

[0052] (4) Zinc treatment; The sherardizing agent is placed on the surface of the steel substrate with a thickness of 5 mm. The sherardizing agent and the steel substrate are then placed in a sherardizing furnace together, heated to 405°C, kept warm for 3 hours, cooled to 180°C with the furnace, and then air-cooled to room temperature.

[0053] (5) Oscillating laser melting treatment; The surface of the steel substrate after zinc infiltration was subjected to a swing-free laser melting treatment, with a laser power of 1000 W, a spot diameter of 0.5 mm, a scanning speed of 5 mm / s, and an overlap rate of 30%.

[0054] The processing results of various embodiments and comparative examples are shown in Table 1.

[0055] Table 1 Performance of the infiltration layer obtained in various embodiments and comparative examples

[0056] It can be seen from Table 1 that compared with non-oscillating laser melting, the thickness and hardness of the carburized layer after oscillating laser melting treatment increased, the wear amount after friction and wear test decreased, and the wear resistance of the carburized layer was improved. After the electrochemical corrosion test, the self-corrosion current density decreased, the self-corrosion voltage increased, the corrosion tendency and corrosion rate decreased, and the corrosion resistance of the carburized layer was improved.

[0057] This is mainly because the present invention uses an oscillating laser melting process, and under the action of laser energy and high-temperature molten pool, the iron atoms further diffuse outward and combine with zinc atoms, thereby increasing the penetration depth of zinc. At the same time, under the action of laser oscillation, the molten pool forms a vortex along the oscillating path of the laser, causing the molten pool to produce a stirring effect, forming a more stable and uniform zinc-diffused layer on the surface of the steel material after zinc-diffused, and the grains are further refined after remelting. At the same time, the rapid cooling of the surface after melting is equivalent to quenching, which increases the hardness of the zinc-diffused layer. On the other hand, it limits the diffusion of zinc atoms out of the substrate, thereby improving the surface roughness of the substrate. Therefore, the present invention uses an oscillating laser melting process to improve the hardness, wear resistance and corrosion resistance of the surface of the steel material.

[0058] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for preparing a wear-resistant and corrosion-resistant composite infiltration layer, characterized in that: The wear-resistant and corrosion-resistant composite infiltration layer is applied on a steel substrate, comprising the following steps: Using a sherardizing agent to sherardize the steel substrate; The steel substrate after the zinc infiltration treatment is subjected to an oscillating laser melting treatment to obtain a wear-resistant and corrosion-resistant composite infiltration layer.

2. The method for preparing a wear-resistant and corrosion-resistant composite infiltration layer according to claim 1, characterized in that: The material of the steel matrix is ​​35CrMo or Q345R.

3. The method for preparing a wear-resistant and corrosion-resistant composite infiltration layer according to claim 1, characterized in that: Before the steel substrate is subjected to the zinc infiltration treatment, the steel substrate is subjected to the degreasing treatment with ethyl acetate at 300°C to 400°C for 20 to 40 minutes and washed with water, then subjected to the laser rust removal treatment and washed with water, and finally dried at 280°C to 350°C for 2-2.5 hours.

4. The method for preparing a wear-resistant and corrosion-resistant composite infiltration layer according to claim 3, characterized in that: The specific settings of the laser rust removal treatment are: laser power of 100-300 W, spot diameter of 4-5 mm, scanning speed of 100-200 mm / s, and overlap rate of 50%-70%.

5. The method for preparing a wear-resistant and corrosion-resistant composite infiltration layer according to claim 1, characterized in that: The raw materials for preparing the zirconizing agent include, by mass fraction, 60% to 80% zinc powder, 5% to 15% aluminum powder, 2% to 10% magnesium powder, 1% to 2% ammonium chloride, and the balance aluminum oxide.

6. The method for preparing a wear-resistant and corrosion-resistant composite infiltration layer according to claim 5, characterized in that: Before the steel substrate is subjected to the sherardizing treatment by using the sherardizing agent, the sherardizing agent is prepared by using the raw materials for preparing the sherardizing agent. After the sherardizing agent is prepared, the prepared sherardizing agent is dried, and the steel substrate is subjected to the sherardizing treatment by using the dried sherardizing agent.

7. The method for preparing a wear-resistant and corrosion-resistant composite infiltration layer according to claim 6, characterized in that: The drying treatment is specifically as follows: heating the prepared zincizing agent to 250° C. to 350° C., keeping the temperature for 1 to 2 hours, cooling it to 180° C. to 220° C. with a heating device, and then air cooling it to room temperature.

8. The method for preparing a wear-resistant and corrosion-resistant composite infiltration layer according to claim 1, characterized in that: The sherardizing treatment is specifically as follows: placing a sherardizing agent on the surface of the steel substrate, the thickness of the sherardizing agent is 5-10 mm, and then placing the sherardizing agent and the steel substrate together in a sherardizing device, heating to 405°C to 445°C, keeping the temperature for 3 to 5 hours, cooling to 180°C to 220°C with the sherardizing device, and then air cooling to room temperature.

9. The method for preparing a wear-resistant and corrosion-resistant composite infiltration layer according to claim 1, characterized in that: The oscillating laser melting treatment is specifically: performing oscillating laser melting treatment on the surface of the steel substrate after the zinc infiltration treatment, and then air cooling to room temperature, wherein the laser power is 1000~1500W, the oscillation amplitude is 0.5~1.5mm, the oscillation frequency is 100~200Hz, the spot diameter is 2mm or 0.2~0.5mm, the scanning speed is 5~15mm / s, and the overlap rate is 30%~50%.

10. The method for preparing a wear-resistant and corrosion-resistant composite infiltration layer according to claim 9, characterized in that: During the oscillating laser melting process, the oscillation mode is linear, single circular, double circular, infinite or figure 8.

11. A wear-resistant and corrosion-resistant composite infiltration layer, characterized in that: The method is prepared by any one of claims 1 to 10.

12. Application of the wear-resistant and corrosion-resistant composite infiltration layer according to claim 11 in electric power fittings.

Citation Information

Patent Citations

  • Multi-element alloy zinc-impregnation method

    CN104498868A

  • Preparation method of modified layer and steel member

    CN107557536A

  • Anti-oxidation carbon-containing zinc impregnation agent and anti-oxidation zinc impregnation process

    CN114875356A

  • Preparation method of wear-resistant and corrosion-resistant protective layer

    CN117802447A